If it's not what You are looking for type in the equation solver your own equation and let us solve it.
24x-2=6(4x+4)
We move all terms to the left:
24x-2-(6(4x+4))=0
We calculate terms in parentheses: -(6(4x+4)), so:We get rid of parentheses
6(4x+4)
We multiply parentheses
24x+24
Back to the equation:
-(24x+24)
24x-24x-24-2=0
We add all the numbers together, and all the variables
-26!=0
There is no solution for this equation
| 3+9(6+4b)=-9b-4(-5-2b) | | 2a-3=4+11(a+1) | | w4– 2= 1 | | -1/3(9x+15)=46 | | 3x-5=2(x+3)= | | h4–2=1 | | c÷9=3 | | -2x+3(1+8x)=-195 | | 5x-(3x-34)=0 | | h4– 2= 1 | | 10k^2+9k+2=0 | | -8d+-7d–-16=-14 | | -128+9x=32+14x | | 5x+9=3x=7 | | -6(3x+6)=-36+4x | | 32.96-p=28.32 | | -48=-3-3p+5(-9-6p) | | 15x=110 | | (2x-10)+20=90 | | 4(m+2.5=7.5 | | 5x+23x-5=7(4x+4) | | -10z-13=10z=15+20z | | 2m+12=3m–31 | | 5/6x+5=10 | | 7x+3=7x+5 | | 3x=4x-2.25 | | 4/5x=-1/3 | | 3x+10(8-10x)=371 | | 230+p=1265 | | -8(7p+8)+8=5+5p | | 3x+-x+4=-6 | | 5/9=6/y |